PERBANDINGAN PENGARUH TERAPI ADJUVANT CONSTRAINT INDUCED MOVEMENT THERAPY DENGAN REPETITIVE TRANSCRANIAL MAGNETIC STIMULATION TERHADAP FUNGSI MOTORIK EKSTREMITAS ATAS PADA PASIEN STROKE ISKEMIK - Tarigan, Ngalasantaru Janstar; Umbas, David Gunawan; Bintang, Andi Kurnia; Tammasse, Jumraini; Amran, Muhammad Yunus; Bahar, Ashari; Zainuddin, Andi Alfian; Halim, Wijoyo (Molucca Medica, 2024)
Introduction Stroke is an acute disorder of cerebral perfusion or vascularization. Stroke patients commonly encounter numerous functional disorders, such as motor, psychological or behavioral disorders, where the most typical symptom is hemiparesis which greatly affects their ability to carry out daily life activities. Repetitive Transcranial Magnetic Stimulation (rTMS) is one of the interventions proposed to improve stroke recovery. Constraint-Induced Movement Therapy (CIMT) is a neurological rehabilitation treatment designed to improve upper extremity motor function after stroke Objective: This study aims to compare the effectiveness of rTMS with CIMT in improving upper extremity motor function in ischemic stroke patients. Research Methodology: This is an experimental clinical trial study with a randomized pre-test post-test control group design on 30 ischemic stroke patients at Wahidin Sudirohusodo General Hospital Makassar and other network hospitals. Repetitive Transcranial Magnetic Stimulation was carried out for 10 stimulations, CIMT was carried out for 30 days. Motor improvement was evaluated by measuring the Fugl Mayer Assessment Upper Extremity (FMA-UE) score Results: The Friedmann test showed that rTMS and CIMT provided significant changes in FMA-UE scores (p: 0.000). Mann Whitney test showed there was a significant difference in FMA-UE scores in the rTMS group compared to CIMT (p: 0.000) Conclusion: There was a significant difference in the FMA-UE score in the rTMS group compared to CIMT. Recommendation: Further research is needed with longer observation and stimulation time and looks at the effectiveness of these two therapeutic modalities through a biomarker so that more objective results can be obtained.